Pengaruh Penggunaan Media Geoboard Dan Puzzle Terhadap Kemampuan Geometri Pada Anak Usia Dini di Kecamatan Mersam Kabupaten Batanghari (Lembaga Pengembangan Kinerja Dosen, 2026)
The purpose of this study was to determine the influence of geoboard and puzzle media on geometry skills in early childhood in Mersam District. The study was conducted at the Melati Integrated Early Childhood Education (PAUD) and An Nisa Early Childhood Education (PAUD) in Mersam District, Batanghari Regency. The study used a quantitative, quasi-experimental approach. Two target groups were compared: one group was given a specific treatment, and the other (the control group) was kept in a specific environment whose effects served as a comparison. The study yielded three conclusions: Geoboard media had an effect on children's geometry skills, with an average increase in scores after use of 51.98. Puzzle media had an effect on children's geometry skills, with an average increase in scores after use of 52.10. Geoboard and puzzle media simultaneously had an effect on children's geometry skills, with calculations in the Sig (Significant) column in the calculation table yielding a sig. 0.845, greater than the probability value of 0.05, or 0.845 > 0.05, indicating that the path analysis coefficient was significant. The study concluded that all three hypotheses were accepted, namely that there was an influence of the independent variables on the dependent variable, both partially and simultaneously. The implication of the study is that the use of geoboard and puzzle media can improve and influence geometry skills in early childhood in Mersam District, Batanghari Regency.